Family functioning and dental trauma, malocclusion and anthropometry in adolescents - Adelaine Maria de Sousa; Thais Carine Lisboa Silva; Bruna de Carvalho Vaigel; Roberto Carlos Mourão Pinho; Renata Cimões (Universidade Estadual de Campinas, 2021)
Aim: The aim of the study was to investigate perceived family cohesion and adaptability and its association with trauma, malocclusion and anthropometry in school adolescents. Methods: Cross-sectional study with a representative sample of 921 adolescents from 13 to 19 years old of both sexes, enrolled in state public schools of a northeastern Brazilian municipality. A questionnaire with sociodemographic questions, the FACES III scale was applied and a clinical oral examination (dental trauma and malocclusion) and anthropometric (BMI by age) were performed. For statistical analysis, was evaluated by the Chi-square test. The variables that presented significance in the bivariate analysis of up to 25% were taken to the multivariate analysis (multinomial logistic regression), variables that presented significance in bivariate analysis of up to 25% were taken to multivariate analysis and all conclusions were drawn considering the significance level of 5%. Results: As a result, it was identified that displaced families were associated with low maternal education, agglutinated families associated with the absence of caries. Rigid families were associated with marked overjet and caries. The prevalence of dental trauma (37.5%) was considered high. Conclusion: It was concluded that family cohesion and adaptability were associated with oral health and socioeconomic factors.